2016
DOI: 10.1016/j.jval.2016.08.212
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Dapagliflozin Versus Acarbose as A Monotherapy in Type 2 Diabetes in China

Abstract: ObjectiveTo estimate the long-term cost-effectiveness of dapagliflozin versus acarbose as monotherapy in treatment-naïve patients with type 2 diabetes mellitus (T2DM) in China. MethodsThe Cardiff Diabetes Model, an economic model designed to evaluate the cost-effectiveness of comparator therapies in diabetes was used to simulate disease progression and estimate the long-term effect of treatments on patients. Systematic literature reviews, hospital surveys, meta-analysis and indirect treatment comparison were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Previous studies have indicated that, in T2DM patients who were no longer responsive to diet and exercise, the dapagliflozin monotherapy was dominant compared with glimepiride and acarbose in the Chinese setting. Both of them indicated that weight control was the most influential factor affecting the economic outcome [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that, in T2DM patients who were no longer responsive to diet and exercise, the dapagliflozin monotherapy was dominant compared with glimepiride and acarbose in the Chinese setting. Both of them indicated that weight control was the most influential factor affecting the economic outcome [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The annually costs of medicine and glucose testing strips were estimated from a large national population-based screening study [26], which interviewed 1482 adults with diabetes at 12 sites in China. Apart from the treatment cost of hyperglycemia, other potential direct health resource utilization, such as the costs of hospitalization and outpatient visits due to their developed complications, also reflected in the simulation, which was extracted directly from published literature or other local sources [4,8,9,[27][28][29]. The cost related to hypoglycemia were estimated from the patient records of two hospitals (Yueyang and Ren JiHospital) in 2016, including 172 patients diagnosed with hypoglycemia who visited the emergency clinic.…”
Section: Costs and Utilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The model uses the 68 or 82 risk equations from the UK Prospective Diabetes Study (UKPDS) to estimate the risk of clinical endpoints and predict the occurrence of diabetes‐related complications and mortality . The present study used the UKPDS 68‐equation model as these equations are widely implemented in diabetes modelling and are extensively tested and validated compared with the UKPDS 82 equations . A sensitivity analysis was performed using the latter model.…”
Section: Methodsmentioning
confidence: 99%
“…The annual costs of medicine and glucose testing strips were originated from a large scale population-based study [27]. The costs of inpatient and outpatient visits due to vascular complications were extracted directly from publications [4,[28][29][30][31][32]. The expense of severe hypoglycemic events was derived from a Chinese costing study, which included 275 patients who incurred hypoglycemic episode [33].…”
Section: Costs and Utilitymentioning
confidence: 99%